Formulation and Evaluation of Natural Pigmented Lipstick from Roselle Flower and Secang Wood Extracts - Monica, Eva; Yoedhistira, Chresiani Destianita; Wulandari, Cindy Dwi (Journal of Fundamental and Applied Pharmaceutical Science, 2024)
Lipstick is a cosmetic product for the lips consisting of pigments, oils, waxes, and moisturizers. Natural lipstick is safe to use and contains natural nutrients to maintain lip health. The use of synthetic dyes in lipstick can have adverse effects on the skin and health; hence, the use of natural dyes from various natural sources needs to be considered. Secang wood and Rosella flowers are plants with important compound contents that have antioxidant properties. Secang wood contains brazilin, alkaloids, flavonoids, saponins, tannins, phenylpropane, and terpenoids. Meanwhile, Rosella flowers that grow in tropical areas have anthocyanin pigments as part of flavonoids that function as antioxidants. This research aims to determine the formulation of lipstick containing extracts of Secang wood and Rosella flowers and to test the antioxidant activity of the preparation. Extraction was carried out by maceration using 70% ethanol solvent. Then, a phytochemical analysis was conducted to determine the extract content, and a lipstick formula was made by comparing the ratio of Rosella and Secang extracts. The optimal formula selection was performed using the Simplex Lattice Design method with quality testing parameters, including pH, melting point, hardness, and antioxidant activity of the preparation. The data analysis showed that the optimal ratio of the two extracts was 2.5% and 7.5% for Rosella and Secang extracts, respectively. At this composition, the optimum pH value was 5, the melting point was 57˚C, the hardness was 1.87 seconds, and the antioxidant activity was classified as strong.